Antioxidant and Antibacterial Activities of Magnesium Oxide Nanoparticles Prepared using Aqueous Extract of Moringa Oleifera Bark as Green Agents - Hanif Amrulloh; Awalul Fatiqin; Wasinton Simanjuntak; Hapin Afriyani; Annissa Annissa (Pandawa Institute, 2021)
In this research, magnesium oxide nanoparticles (MgONPs) was prepared from MgCl2 solution using aqueous extract of Moringa oleifera (M. oleifera) bark as green agent. Preparation procedure involved mixing of MgCl2.6H2O solution and the aqueous extract of M. oleifera bark, followed by drop wise addition of NaOH solution. The formation of MgONPs in this study was confirmed using UV-Vis absorption. The spherical crystal structure of MgONPs was confirmed by XRD analysis. The average particle size of the synthesized MgONPs was found between 60—100 nm using SEM and TEM images and PSA results. The MgONPs synthesized showed good antioxidant activity, as well as antibacterial activity against S. aureus, E. faecalis, E. coli, and S. dysenteriae bacteria.